Upgrading of sulfur-containing biogas into high quality fuel via oxidative coupling of methane - Gu, Sangseo; Choi, Jae-Wook; Suh, Dong Jin; Park, Young-Kwon; Choi, Jungkyu; Ha, Jeong-Myeong (WILEY, 2021)
Biogas, which contains methane (CH4), carbon dioxide (CO2), hydrogen sulfide (H2S), and other minor compounds, is a promising energy source and chemical feedstock (not least because it is generated from waste); however, its application as fuel is limited because of its low calorific value, which can be mitigated by upgrading biogas to high-quality fuels via the oxidative coupling of methane (OCM), a catalytic process that increases its higher heating value from 39.9 (CH4, Wobbe index = 53.5 MJ/Nm(3)) to 41.7 MJ/Nm(3) (OCM product mixture, Wobbe index = 54.4 MJ/Nm(3)), thus achieving compliance with the fuel standards in many countries (Wobbe index = 45.5-55.0 MJ/Nm(3)). Among the compounds produced during OCM, H2S is formed in minor amounts but strongly suppresses biogas valorization, mainly because of potential catalyst poisoning. To understand the effects of sulfur compounds on OCM catalysts, three such catalysts, namely perovskites (SrTiO3 and LaAlO3) and Na2WO4/Mn/SiO2 (NWM), were used to convert biogas into olefins and paraffins. The oxidation of H2S in biogas produced sulfur dioxide, which did not strongly affect NWM but was strongly adsorbed by perovskites and, in turn, significantly reduced their OCM activity. Furthermore, long-term (100 hours) stability testing demonstrated that the OCM activity of NWM was stable in the presence of H2S. Consequently, the influence of sulfur compounds on the catalysts during the OCM process was elucidated, including catalyst poisoning via sulfur species adsorption. The strategy to suppress the detrimental effects of sulfur poisoning was suggested, which can contribute to the development of feasible process for valorizing biogas to high quality fuels and chemicals.
Keywords: ANAEROBIC-DIGESTION; HYDROGEN-PRODUCTION; CATALYSTS; OXYGEN; MN/NA2WO4/SIO2; CONVERSION; ETHYLENE; METAL; DIMERIZATION; TRANSITION